R&D capitalisation: Where did we go wrong? - Mark de Haan; Joseph Haynes (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2018)
This paper is an attempt to contribute to the discussion of research and development (R&D) capitalisation in the system of national accounts. The paper first spells out under which conditions knowledge creation truly leads to fixed assets in the national accounts sense. As a next step, R&D capitalisation is examined in the context of globalisation. One of the serious problems that multinational enterprise (MNE) groups present for macro-economic measurement is the issue of assigning economic ownership of R&D, and intellectual property (IP) more generally, to the various fractions of a global value chain and therefore to domestic economies. This is an issue for which international guidance is currently incomplete and still under research by national accountants. In this paper the discussion of IP focuses largely on R&D. By analysing real world companies and their production processes this paper aims to highlight some of the issues with the current recording treatment around IP. This translation of information on the MNE group's business structure to the national accounts framework will give an indication of real world distortions that national accountants may encounter when measuring the activities of MNE groups on a domestic economy basis. All the information contained within this paper relating to these MNE groups is taken from previously published publically available sources. There may be deficiencies in the way the characteristics of these MNE group structures are being revealed by these sources. We nevertheless take these available sources as the starting point of this paper with the main purpose of highlighting the complexities of recording these structures in the national accounts. This paper offers a number of proposals for improvements though definite solutions to the issues are not possible in one paper alone. Perhaps the greatest contribution of this paper is in highlighting clearly the need for openness and data sharing between national statistics institutes (NSIs). Accurate recording of the activities of MNE groups requires cooperation and data sharing at a far greater level than NSIs have previously been willing to do.
Keywords: E01; F62; 330; national accounts; intellectual property; globalisation